Effectiveness of practice in gymnastics and the process of physical education of students (SCIENCE and SOCIETY, 2025)
The article studies the effectiveness of gymnastics practice within the framework of school physical education, analyzing historical perspectives, pedagogical strategies, and modern research results. Through a comprehensive literature review and discussion of current methodologies, the article identifies important conditions for improving the